Accuracy of patient self‐report as a measure of inhaled asthma medication use. Issue 3 (21st March 2013) - Patel, Mitesh; Perrin, Kyle; Pritchard, Alison; Williams, Mathew; Wijesinghe, Meme; Weatherall, Mark; Beasley, Richard
<x xml:space="preserve">Abstract</x> Self‐report and electronic monitoring are two methods to measure adherence to inhaled asthma therapy. Patients who underuse treatment overreport their actual use, while patients who overuse their treatment underreport their use. Knowledge of the inaccuracy of self‐report is important in informing clinicians utilizing this method to assess treatment adherence.